ANALISIS PENGARUH KETIDAKTEPATAN KODE DIAGNOSIS DAN KODE TINDAKAN PASIEN RAWAT INAP PESERTA JAMINAN KESEHATAN NASIONAL TERHADAP TARIF DI RUMAH SAKIT UMUM DAERAH WANGAYA KOTA DENPASAR - Yohana Fransiska Nanjo (Health Care Media, 2022)
Coding inaccuracy is a form of discrepancy in the writing of disease diagnoses and actions with the classifications set out in the ICD-10 and ICD-9 CM. Coding is one part of the medical record installation that deals with coding disease diagnoses and actions given to patients based on ICD-10 and ICD-9 CM. This study aimed to determine the effect of the inaccuracy of the diagnosis code and the code of action of inpatients of JKN participants on the rates at the Wangaya Regional General Hospital (RSUD) Denpasar City. Based on the results of initial observations in June 2021, It returned 132 files to claim files of JKN inpatients at Wangaya Hospital, Denpasar City. The type of research used in this study is quantitative analytic with a cross-sectional, the population in this study was 1,079 medical records, and the sample of this study was 132 medical records, and research instruments used office stationery, notebooks, observation guidelines, checklists, and medical records. Inpatients participated in JKN, ICD-10, and ICD-9 CM, information systems at Wangaya Hospital, Denpasar City. The data analysis technique used univariate and bivariate analysis. The results of this study from 132 claim files of inpatient JKN participants obtained 90 (68.2%) inaccuracies in the diagnosis code and 85 (64.4%) inaccuracies in the regulation of activities, and 80 (60.6%) incorrect rates file. The conclusion of this study showed that there was a significant effect of the inaccuracy of the diagnosis code and the inaccuracy of the code of action on hospital rates for JKN inpatients with a p-value of 0.000 <0.05 on the inaccuracy of the diagnosis code and there is a significant effect between the inaccuracy of the code of action on rates hospital at Wangaya Hospital, Denpasar City, with a p-value 0.005 <0.05.